2008
DOI: 10.1161/atvbaha.108.173930
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Response of Initiation of Blood Coagulation by Tissue Factor in Patterned Microfluidic Capillaries Is Controlled by Shear Rate

Abstract: Objective-Blood flow is considered one of the important parameters that contribute to venous thrombosis. We quantitatively test the relationship between initiation of coagulation and shear rate and suggest a biophysical mechanism to understand this relationship. Methods and Results-Flowing human blood and plasma were exposed to cylindrical surfaces patterned with patches of tissue factor (TF) by using microfluidics. Initiation of coagulation of normal pooled plasma depended on shear rate, not volumetric flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
119
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 49 publications
9
119
2
2
Order By: Relevance
“…removal of thrombin and fibrin monomers. 37 In accordance with our results, it has been shown that the thrombi formed in mesenteric venules after laser injury are surrounded by a fibrin cap. …”
supporting
confidence: 93%
See 1 more Smart Citation
“…removal of thrombin and fibrin monomers. 37 In accordance with our results, it has been shown that the thrombi formed in mesenteric venules after laser injury are surrounded by a fibrin cap. …”
supporting
confidence: 93%
“…30 Single-pass flow perfusion likely makes the difference here because under flow, the deposited platelets provide a rate-limiting surface for the formation of thrombin and subsequent fibrin, whereas the same flow removes procoagulant factors and hence restricts fibrin formation. 37 Remarkably, in reconstitution experiments, the addition of both platelets and red blood cells was required for complete reversal of dilution effects. By implication, this indicates that under conditions of flow and sufficient margination of platelets by red blood cells, a coagulant activity of >60% is required for unrestricted generation of fibrin.…”
Section: Effects Of Hemostatic Insufficienciesmentioning
confidence: 99%
“…Staining was slightly more intense in thrombi from saphenous vein than carotid artery, consistent with higher fibrin production in lower shear conditions. 27 Both carotid artery and saphenous vein thrombi from mice infused with human fibrinogen demonstrated more intense fibrin staining at the periphery of proteinaceous regions and intense, diffuse staining in regions containing erythrocytes (Figure 2). These findings suggest that hyperfibrinogenemia increased thrombus fibrin content in both high and low shear vessels.…”
Section: Elevated Fibrinogen Increases the Fibrin(ogen) Content Of Thmentioning
confidence: 99%
“…Thrombi from saphenous veins appeared more fibrin-rich than thrombi from carotid arteries (Figure 2), consistent with observations that lower shear promotes fibrin deposition. 27 Notably, however, hyperfibrinogenemic mice demonstrated shortened TTOs and increased fibrin content in thrombi in both high and lower shear vessels (Figures 1, 2). These findings do not diminish a role for stasis in thrombosis but rather suggest that the contributions of shear are eclipsed in the setting of hyperfibrinogenemia and potentially other pathologies as well.…”
mentioning
confidence: 92%
“…Low shear rate recirculation zones in the peristrut regions can entrap activated platelets where longer residence times retain coagulation factors to increase the probability of coagulation [10,37]. Thus, high shear rates on the surface of the strut and low shear rates in the peristrut recirculation zones are synergistic for thrombus formation.…”
Section: Discussionmentioning
confidence: 99%